2009
DOI: 10.1179/135100009x12525712409652
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Prdx6 and resistance to peroxide-induced death in Hepa1-6 cells: Prdx suppression increases apoptosis

Abstract: Peroxiredoxins are thiol-specific antioxidants that catalyze the reduction of cellular peroxides and protect cells from ROS-mediated damage and death. Peroxiredoxin gene expression is up-regulated in a number of cancers, suggesting a possible role in cancer cell maintenance. Prdx6, a cytoplasmic protein elevated in certain cancers, is highly expressed in liver and transcriptionally regulated by various oxidative stresses. In the present study, we found that the cancerous Hepa1-6 hepatoma cell line is significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 40 publications
2
29
0
1
Order By: Relevance
“…Furthermore, visualization of nuclear fragmentation by DAPI staining revealed that the nuclear fragmentation in the siR-PRDX6 transfected groups of all HSA cell lines was significantly increased compared with that of the control siRNA-transfected group. Consistent with our findings, previous transient transfection of Hepa1e6 cells with PRDX6 siRNA was shown to lead to a marked reduction in its expression and an increase in peroxide-induced cytotoxicity mediated by apoptosis; these results suggested that PRDX6 upregulation might be a tumour-supportive adaptation in cancer (Walsh et al, 2009). …”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, visualization of nuclear fragmentation by DAPI staining revealed that the nuclear fragmentation in the siR-PRDX6 transfected groups of all HSA cell lines was significantly increased compared with that of the control siRNA-transfected group. Consistent with our findings, previous transient transfection of Hepa1e6 cells with PRDX6 siRNA was shown to lead to a marked reduction in its expression and an increase in peroxide-induced cytotoxicity mediated by apoptosis; these results suggested that PRDX6 upregulation might be a tumour-supportive adaptation in cancer (Walsh et al, 2009). …”
Section: Discussionsupporting
confidence: 88%
“…PRDX6 is a bifunctional protein with both glutathione peroxidase and iPLA2 activities and is the only mammalian 1-Cys member of the PRDX superfamily [34]. In a recent study, the overexpression of PRDX6 attenuated cisplatin-induced apoptosis in human ovarian cancer cells [11], whereas the reduction of PRDX6 expression increased cell death in liver cancer cells [35]. Invasion-and metastasispromoting actions of PRDX6 have been found in lung cancer cells [10,36].…”
Section: Discussionmentioning
confidence: 97%
“…For example, ACAT1 (21,22) and ECHS1 (23,24) may be involved in lipid metabolism, whereas ATP6V1A and ATP6V1B2 mediate Hϩ transport (25,26). PRDX3 (27,28) and PRDX6 (29,30) have antioxidant effects, regulating apoptosis and cell damage by way of DLD (31). SUCLG2, SUCLA2, and TPI1 (32) play a role in ATP and/or GTP metabolism.…”
Section: Discussionmentioning
confidence: 99%